2023
DOI: 10.1371/journal.pntd.0011440
|View full text |Cite
|
Sign up to set email alerts
|

ELISA F29 –A therapeutic efficacy biomarker in Chagas disease: Evaluation in pediatric patients treated with nifurtimox and followed for 4 years post-treatment

Abstract: Background Measurement of the success of antitrypanosomal treatment for Chagas disease is difficult, particularly in the chronic phase of the disease, because anti-Trypanosoma cruzi antibodies persist in serum for prolonged periods. We studied the effects of nifurtimox administered by two different treatment regimens on the T. cruzi calcium-binding flagellar protein F29 in children diagnosed with Chagas disease measured using an enzyme-linked immunosorbent assay (ELISA) technique (ELISA F29). Methods and pri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…cruzi (mothers) were considered, α-Gal seroprevalence increased up to ∼70–80%, well in the range of other T . cruzi antigens proposed as post-therapeutic biomarkers for Chagas disease [ 18 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…cruzi (mothers) were considered, α-Gal seroprevalence increased up to ∼70–80%, well in the range of other T . cruzi antigens proposed as post-therapeutic biomarkers for Chagas disease [ 18 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Most remarkably, of 24 patients belonging to Group 3 (3 to 16 years-old children), 14 (58.3%) achieved negative seroconversion for α-Gal-ELISA whereas none of them negativized for conventional serology. The difficulty in achieving post-treatment negativization using conventional serological methods in children aging >3 years (and also in chronically infected adults) constitutes a major issue in the clinical management of Chagas disease, and stresses the urgent need of surrogate drug efficacy indicators [7,31,44,45]. In addition to providing a novel tool to shorten follow-up periods after chemotherapy, the α-Gal-ELISA developed here may also assist T. cruzi infection diagnosis in certain clinical situations.…”
Section: Plos Neglected Tropical Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, the T. cruzi Ca 2+ -binding flagellar protein F29 has been extensively studied as an early marker of response to treatment with parasiticidal drugs in samples from treated patients. A significant decrease in antibodies against the anti-F29 antigen in an in-house ELISA was noted when monitoring the response to drug treatments [45], and although a low specificity has been detected [46], recent results have shown that 77.2% of T. cruzi-infected children treated with a 60-day regimen with Nifurtimox seroconvert for ELISA-F29 [47].…”
Section: Discussionmentioning
confidence: 99%